2021
DOI: 10.1186/s12875-021-01426-8
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in general practice; a questionnaire study on the GPs role and guideline implementation in Norway

Abstract: Background Patients in need of palliative care often want to reside at home. Providing palliative care requires resources and a high level of competence in primary care. The Norwegian guideline for palliative care points to the central role of the regular general practitioner (RGP), specifying a high expected level of competence. Guideline implementation is known to be challenging in primary care. This study investigates adherence to the guideline, the RGPs experience with, and view of their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
(18 reference statements)
4
10
0
Order By: Relevance
“…The tendency for rural GPs to be more involved than urban GPs in palliative care must be interpreted with caution due to our sample size. This is, however, in line with our previous questionnaire study, showing that rural GPs to a larger degree reported to be central in palliative care [ 25 ]. In an Australian study, rural and remote GPs were found to have more responsibility for their palliative patients and less support from the PCTs than their urban colleagues [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The tendency for rural GPs to be more involved than urban GPs in palliative care must be interpreted with caution due to our sample size. This is, however, in line with our previous questionnaire study, showing that rural GPs to a larger degree reported to be central in palliative care [ 25 ]. In an Australian study, rural and remote GPs were found to have more responsibility for their palliative patients and less support from the PCTs than their urban colleagues [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Norway, although conforming to national legislation, the practical organization of primary care in different municipalities varies, and steps to accommodate for a longer travel distance from the hospital may be appropriate. For the hospital specialists, however, our findings seem like a departure from the ideal of equality of services, strengthening our suggestion of unwarranted variation in the specialist service provision from the findings in our previous study [ 25 ]. These connections may need further investigation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In a previous paper from this study, we found that there were unfortunate variations in palliative knowledge and skills among GPs [ 19 ]. This could be because each GP has few patients needing palliative care and limited experience could make it difficult to maintain knowledge and skills [ 31 ]. In addition, some patients continue to be followed up by specialist palliative care even after discharge, especially if they live close to a hospital [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Switzerland and Norway, a study found low overall adherence to current practice guidelines and high variation in the use of nutritional therapy in patients undergoing stem cell transplantation [ 11 ]. A study carried out in Norway showed low adherence of regular general practitioners to the palliative care guideline [ 12 ]. In the management of osteoarthritis, studies suggest that the main approaches recommended in the guidelines are underutilized and that the quality of care is inconsistent [ 13 ].…”
Section: Introductionmentioning
confidence: 99%